Development of training guide for inappropriate sexual behaviors among children with neurodevelopmental disorders in inclusive settings - Kiran Hussain; Aasma Yousaf; Fareeha Latif (JIE, 2025)
This study aimed at qualitative investigation of management techniques for inappropriate sexual behaviors among children with neurodevelopmental disorders in inclusive settings. Sample was recruited by using purposive criterion sampling technique. Data was collected through semi-structured interviews which were then audio recorded and transcribed and analyzed via thematic analysis. Results consisted of one main theme of management techniques with nine subthemes which included Psychoeducation for teachers, Sex education for Children, Parental guidance, Diversion, Physical Activity, Social stories, Dress Modification, Differential reinforcement and Video modeling.